Prevalence of chronic gingivitis cases at the East Selemadeg I Community Health Centre in Tabanan, Bali, from January 2024 to March 2025: Prevalensi kasus gingivitis kronis di Puskesmas Selemadeg Timur I Tabanan Bali pada Januari 2024-Maret 2025 - Sujana, Kadek Arista Dwiputra; Pratama, I Wayan Agus Wirya; Kusumadewi, Ni Wayan Adi (Makassar Dental Journal PDGI Makassar, 2025)
Gingivitis is a common oral disease with a high prevalence in Indonesia. Educational and promotional efforts are needed to raise awareness among the public, especially adolescents, about preventing gingivitis. This observational study used a cross-sectional methodology, showing the highest number of cases recorded in October 2024 (16.4%). Of the total 49 cases, 71.5% were fe-male patients. Based on age, most patients with gingivitis were in the 19-40 age range (63.3%). This condition indicates that hor-monal status in women can affect the condition of gingival tissue. It is concluded that gingivitis cases at the Selemadeg Timur I Health Centre are more commonly experienced by women and, based on age, most frequently occur in the 19-40 age range.